2020
DOI: 10.3390/nu12103123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifidobacterium animalis Subsp. lactis (BPL1) Supplementation in Children and Adolescents with Prader–Willi Syndrome: A Randomized Crossover Trial

Abstract: Prader–Willi syndrome (PWS) is a rare genetic disorder characterized by a wide range of clinical manifestations, including obesity, hyperphagia, and behavioral problems. Bifidobacterium animalis subsp. lactis strain BPL1 has been shown to improve central adiposity in adults with simple obesity. To evaluate BPL1′s effects in children with PWS, we performed a randomized crossover trial among 39 patients (mean age 10.4 years). Participants were randomized to placebo–BPL1 (n = 19) or BPL1–placebo (n = 20) sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…This non-significant trend provides additional evidence in support of the findings by Amat-Bou et al that Lact. reuteri improves insulin signaling and, in this way, promotes normal weight [15]. However, while the probiotic study conducted by Amat-Bou et al demonstrated such positive effects in individuals with PWS using the Bifidobacterium strain BPL1, it is unsurprising that such effects are also observed in the present study of LR-99, as both Bifidobacteria and Lactobacilli have important interconnected functional roles in the gut such as fructose and oligosaccharide metabolism [52].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This non-significant trend provides additional evidence in support of the findings by Amat-Bou et al that Lact. reuteri improves insulin signaling and, in this way, promotes normal weight [15]. However, while the probiotic study conducted by Amat-Bou et al demonstrated such positive effects in individuals with PWS using the Bifidobacterium strain BPL1, it is unsurprising that such effects are also observed in the present study of LR-99, as both Bifidobacteria and Lactobacilli have important interconnected functional roles in the gut such as fructose and oligosaccharide metabolism [52].…”
Section: Discussioncontrasting
confidence: 48%
“…One recent study found that Lact. reuteri administration in the PWS population improved insulin sensitivity and decreased abdominal adiposity in children older than 4.5 years of age [15]. However, the mechanisms involved in the induction of such effects remain unclear and may manifest in many different bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a literature review up until July 2021 was carried out using PubMed database searches with the following terms: "Prader-Willi syndrome" and "gut/intestinal microbiome/microbiota". We identified 13 publications that included both observational [25][26][27][28] and interventional studies [29][30][31][32][33], a study protocol [34], and three studies based on secondary analyses of microbiome data from previously published articles [35][36][37]. Publications were classified based on their evidence level in accordance with the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology, considering the lowest evidence level "Expert opinion" (score 4) and the highest evidence level "High quality meta-analysis, systematic reviews of randomized controlled trials (RCTs), or RCTs with a very low risk of a bias" (score 1 ++ ) [38].…”
Section: The Gut Microbiome In Health and Diseasementioning
confidence: 99%
“…To this date, four randomized controlled clinical studies have evaluated the effects of probiotic supplementation in individuals with PWS using two different bacterial species, namely B. lactis and L. reuteri without significant adverse events (Table 2) [30][31][32][33]. Additionally, a study implementing a dietary intervention with prebiotics and a fiber-rich diet has also been reported [29].…”
Section: Targeting the Gut Microbiome As A Therapeutic Approach For Prader-willi Syndromementioning
confidence: 99%